RANCANG BANGUN PERANGKAT KERAS SISTEM PEMANTAU POTENSI TANAH LONGSOR DENGAN WIRELESS SENSOR NETWORK BERBASIS LORA - Poetra, Andreas Genta Exna; Wagyana, Agus; Febrian, Muhamad Reza (Spektral, 2024)
Landslides represent one of the natural disasters that cause extensive harm to communities, affecting them morally and materially. Various parties, including the government, have implemented various efforts to prevent and reduce the impact of landslides. Because landslide potential areas are difficult to do directly, a tool is designed that is able to monitor areas that have the potential for landslides. The purpose of this research is to design hardware and monitor soil movement in a potential landslide location. The device uses ultrasonic sensor and accelerometer sensor to measure the ground movement. Early warning system is made as an effort to provide warnings to local residents if there are indications of land movement that has the potential to become a landslide disaster. In the process of sending data, LoRa module is used. For remote monitoring of soil movement, the data taken by the sensor will be sent to the Thingspeak IoT platform so that soil movement can be monitored in graphical form. This system can send data up to a radius of 1200 meters, and has a fairly low percentage error value below 1% for measurements using ultrasonic sensors and can monitor the movement of tools using accelerometer sensors.